Neonatal Fever as a Digital Emergency: A Clinical Safety Audit of Turkish-Language YouTube Health Information - Elif Keleş Gülnerman; İbrahim Murat Hirfanoğlu (OSMANGAZİ JOURNAL OF MEDICINE, 2026)
To evaluate the clinical accuracy, information literacy, and public health safety of Turkish-language YouTube videos addressing neonatal fever, a cross-sectional content audit was conducted using three Turkish-language search terms. Of 112 screened videos, 24 met neonatal-specific inclusion criteria and were independently evaluated by two neonatologists. Video quality was assessed using GQS, JAMA criteria, mDISCERN, CRAAP, PEMAT-U/A, Newborn Fever Safety and Quality Score (NFSQS), and E-GRADE classification. Correlation and multivariable regression analyses identified factors associated with guideline adherence. The 24 videos accumulated 935,427 views. Inter-rater reliability was excellent (κ=0.88). Mean NFSQS was 8.38 ± 5.58 out of 24. Fifteen videos were classified as “Not Differentiate Newborn,” whereas only three were rated “Safe and Useful.” CRAAP score demonstrated a strong positive correlation with NFSQS (rₛ = 0.762, p < 0.001), while view count was negatively associated with the Clinician Safety Index (rₛ = −0.521, p = 0.009). Short-form videos (<1 minute) achieved significantly lower NFSQS scores than longer videos (3.88 ± 3.64 vs 10.62 ± 5.03, p = 0.004). In multivariable analysis, CRAAP score (β = 1.770, 95% CI 1.105–2.435, p < 0.001) and video duration (β = 0.182, p = 0.010) were independently associated with NFSQS. Most Turkish-language YouTube videos on neonatal fever provide inadequate neonatal-specific guidance, potentially contributing to unsafe caregiver decision-making. Information literacy quality and content depth, rather than popularity, determined guideline adherence. The predominance of incomplete short-form content and poor alignment between visibility and clinical quality raise important public health concerns for high-risk neonatal conditions.